An investigation of factors influencing the intention to use mHealth apps for self-care - Azhar F.A.; Dhillon J.S. (Inderscience Publishers, 2023)
This paper reports determines factors that are essential to be considered in the design mHealth apps for self-care. Self-care is an emerging area that refers any intentional actions people take to care for their physical, mental and emotional health. Encouraging people to practice self-care is a challenge and it is known to be an important part of a healing process. There are numerous health support applications in the market that can be downloaded via smartphones. These apps are typically designed to enable healthcare consumers to improve their health or maintain their good health. However, recent research indicates that with the exception of physical activity, more consumers are currently tracking key health factors on paper or in their heads than with mobile applications. We have identified factors that influence the intention to use mHealth apps for self-care via a systematic literature review approach. The factors obtained were further investigated quantitatively by involving 203 consumers. These factors when considered in the design of future mHealth apps could address the requirements and expectation of consumers towards mHealth apps in general and could possibly motivate them to use mHealth continuously in achieving their health goals. 2018 Inderscience Enterprises Ltd.